PATTERN AND TIMING OF SEDIMENT INFILL AT GLACIER-FED MUD LAKE: IMPLICATIONS FOR LATEGLACIAL AND HOLOCENE ENVIRONMENTS IN THE MONASHEE MOUNTAIN REGION OF BRITISH COLUMBIA, CANADA - Hodder K.R.; Desloges J.R.; Gilbert R. (My University, 2006)
The Holocene sedimentary infill of proglacial Mud Lake, British Columbia, Canada, was investigated using 3.5 kHz acoustic sub-bottom profiling and sediment samples. The sediment infill is a mixture of silt and clay and is divided into five stratigraphic units: massive silt (Unit 1), weakly laminated silt with very fine sand beds (Unit 2), weakly laminated silt with rippled beds of fine sand (Unit 3), weakly laminated clay with very fine sand laminations (Unit 4) and silt-clay varves (Unit 5). Acoustic reflectors correlate with stratigraphic unit boundaries. Annual accumulation rates were estimated for six age/depth intervals: prior to 9.6 kyr cal. BP, accumulation rates were very high - on the order of several centimetres per year. Early to middle Holocene sediment inputs (9.6-3.6 kyr cal. BP) were variable but low, ranging from 0.3 mm/yr to 1.2 mm/yr. The late Holocene (most recent 3.6 kyr) shows annual accumulation rates that generally exceed 2 mm/yr. Surface sediment reveals a mean of 4.3 mm/yr over the last 20 years. These results are consistent with regional Holocene chronologies and long-term paraglacial succession: (1) maximum sediment and meltwater availability and minimum stabilization by vegetation following Fraser deglaciation replaced by (2) less meltwater and sediment availability during the Hypsithermal, and (3) more stabilized sediment during the early and mid Holocene. Renewal of glacial activity, particularly in the late Neoglacial, has led to increased rates of accumulation in Mud Lake. Despite the contrasting geologic setting of Mud Lake in the Omineca belt, contemporary sediment yield is consistent with the trend of sediment yield with glacier cover in lakes of the adjacent Foreland belt.
Keywords: GLACIER-FED LAKE; ACOUSTIC RECORDS; SEDIMENT YIELD; VARVES; HOLOCENE CLIMATE; BRITISH COLUMBIA; CANADA; Holocene; Cenozoic::Quaternary::Holocene; Кайнозой::Четвертичная::Голоцен